The teeth of the gale - Aiken, Joan, 1924-2004. (New York : Harper & Row, 1988)
At the request of the nun with whom he is in love, eighteen-year-old Felix embarks on a perilous rescue mission across the strife-torn countryside of Spain in the late 1820s. Sequel to "Go Saddle the Sea" and "Bridle the Wind.".
"A Charlotte Zolotow book.".
Bibliography: p. 306-307.
Booklist.
Horn Book.
School Library Journal.
7.5
Keywords: Adventure and adventurers -- Fiction; Adventure and adventurers -- Fiction; Spain -- Fiction; Spain -- Fiction